TRPC1- and TRPC3-dependent Ca2+ signaling in mouse cortical astrocytes affects injury-evoked astrogliosis in vivo - Belkacemi, Thabet (2017)
Fil: Belkacemi, Thabet. Universität des Saarlandes. Experimentelle und Klinische Pharmakologie und Toxikologie; Alemania